Anime and Japanese: potential improvement of teaching meth- ods on the basis of preliminary survey - Akhapov Y.A.; Baubekkyzy Z. (Journal of Oriental Studies, 2024)
Japanese anime and manga is considered as an integral part of Japa- nese popular culture. In recent years, it began to spread widely throughout the world. Especially, it has a significant impact on the youth identity in the selection of foreign language and increasing the motivation of students to study Japanese language. Unfortunately, this issue has not been studied in Kazakhstan yet. The article discusses the results of a preliminary survey for students to improve the methods of teaching Japanese language with Japanese anime and manga, and analyzed the views of the respondents. Key words: Japanese language, anime, questionnaire survey, teaching methods, 日本語 nihongo, アニメ anime, アンケート anketa, 教授法 kyoujuhou.